Sustained delivery of a novel natriuretic peptide for three weeks with in situ polymer precipitation delivery system - Lim, Soo G. (2013)
CD-NP (Cenderitide) is a chimeric natriuretic peptide that acts on both the A and B natriuretic guanylyl cylcase receptors. This differentiated mechanism of action avoids the hypotensive nature of BNP while retaining the cardiac unloading and renal enhancing actions in heart failure (HF) together with direct anti-remodeling actions. CD-NP is being developed as an outpatient therapy for patients following hospital admission for HF, the “post-acute” period, to reduce rehospitalization. Our objective is to design an in situ polymer precipitation delivery system suitable for the chronic and sustained release of CD-NP.